2006
DOI: 10.1057/palgrave.jibs.8400209
|View full text |Cite
|
Sign up to set email alerts
|

Productivity spillovers from R&D, exports and FDI in China's manufacturing sector

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
207
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(231 citation statements)
references
References 45 publications
8
207
1
3
Order By: Relevance
“…Spillover channels, mediating factors, and FDI heterogeneity coexist and interact in determining the extent of knowledge spillovers. Theoretical and empirical research should therefore try to address them simultaneously (Wei and Liu 2006;Liang, 2008). Does the importance of absorptive capacity for capturing knowledge spillovers through demonstration effects vary with the degree of multinational enterprise ownership?…”
Section: Resultsmentioning
confidence: 99%
“…Spillover channels, mediating factors, and FDI heterogeneity coexist and interact in determining the extent of knowledge spillovers. Theoretical and empirical research should therefore try to address them simultaneously (Wei and Liu 2006;Liang, 2008). Does the importance of absorptive capacity for capturing knowledge spillovers through demonstration effects vary with the degree of multinational enterprise ownership?…”
Section: Resultsmentioning
confidence: 99%
“…In an open economic system, technological progress is made via self-innovation and technological knowledge transfer and spillover through international trade and foreign direct investment (FDI) (Wei and Liu, 2006). However, knowledge transfer and spillovers are never unconditional.…”
Section: Introductionmentioning
confidence: 99%
“…Against this background, a number of studies have been published on the role of FDI in business development, economic growth or technological innovation in China (Wu, 1999;Wei and Liu, 2001;Huang, 2003;Wei and Liu, 2006;Liu and Buck, 2007;Chang and Xu, 2008;Guo, 2008;Wei et al 2008;Liu et al 2009). However, it remains unclear whether there is a minimum threshold of absorptive capacity in China for inward FDI to produce positive spillovers.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies have so far produced mixed results. Some studies showed evidence of positive technology spillovers from FDI to local firms, while other studies found that FDI negatively affects the productivity of local firms (see, for instance, Caves, 1974;Globerman, 1979;Kokko;Blomstrom and Wolff, 1996;Aitken and Harrison, 1999;Djankov and Hoekman, 2000;Kathuria, 2000;Chung, 2001;Chuang, Mitchell and Yeung, 2003;Javorcik, 2004;Wei and Liu 2006;Tian 2007;Buckley, Clegg and Wang 2007). 2 Interestingly enough, both sides in the debate have looked at the issue almost exclusively from the perspective of local firms that receive the spillovers rather than the perspective of TNCs that generate the spillovers.…”
mentioning
confidence: 99%